The impact of a 12-week tele-exercise program on cognitive function and cerebral oxygenation in patients with OSA: randomized controlled trial—protocol study - Stavrou, Vasileios T.; Pitris, Konstantinos; Constantinidou, Fofi; Adamide, Tonia; Frangopoulos, Frangiskos; Bargiotas, Panagiotis (Frontiers in Sports and Active Living, 2024)
Obstructive sleep apnea (OSA) contributes to a number of adverse health effects, particularly on brain health. Chronic sleep disruption caused by OSA could adversely affect cognitive health. Exercise is recommended as a non-pharmacological intervention for patients who are intolerant to continuous positive airway pressure (CPAP) and has been shown to have beneficial effects on brain health and cognitive function. The aim of this protocol is to investigate the effects of a 12-week tele-exercise program on cognitive function and specific parameters of brain activity, including brain metabolism and oxygenation, in patients with OSA. The project aims to demonstrate the multi-dimensional relationship between exercise, cognition and brain oxygenation/metabolism. Our local ethics committee has approved the study. Our population sample (group A = OSA with cognitive impairment (CI) and teleexercise; group B = OSA with CI and no tele-exercise; group C = OSA without CI and no teleexercise) will undergo assessment both before and after a 12-week tele-exercise intervention program. This assessment will include a comprehensive battery of subjective and objective assessment tests. Data will be analysed according to group stratification. We hypothesize a beneficial effect of tele-exercise on sleep and cognitive parameters and we are confident that this study will raise awareness among healthcare professionals of the brain health benefits of exercise in patients with low compliance to CPAP treatment.